2013
DOI: 10.1002/adma.201300020
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Unusual, Highly Conductive Grain Boundaries in High‐Mobility Phase Separated Organic Semiconducting Blend Films Probed by Lateral‐Transport Conductive‐AFM

Abstract: The effect of grain boundaries in high hole mobility organic blend films of diF-TES ADT:PTAA is evaluated using conductive-AFM measurements revealing the presence of unusually conductive grain boundaries. The latter characteristic has not been reported previously for any other organic semiconducting film system and is believed to underpin the excellent and morphology-independent hole transport characteristics seen in these composite films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…[30] This technique consists in scanning the active layer's surface deposited over an insulating substrate, with a platinum-coated (Pt) conductive AFM probe in contact, at a known lateral distance from the second gold (Au) electrode. By applying a fixed bias between the C-AFM probe and the Au electrode, the simultaneous acquisition of both the (7,5) SWNT network topography and the lateral current is possible.…”
Section: Percolation Study Through Lateral Conductivity Measurements mentioning
confidence: 99%
“…[30] This technique consists in scanning the active layer's surface deposited over an insulating substrate, with a platinum-coated (Pt) conductive AFM probe in contact, at a known lateral distance from the second gold (Au) electrode. By applying a fixed bias between the C-AFM probe and the Au electrode, the simultaneous acquisition of both the (7,5) SWNT network topography and the lateral current is possible.…”
Section: Percolation Study Through Lateral Conductivity Measurements mentioning
confidence: 99%
“…[1][2][3][4] The charge carrier mobilities in OFETs now exceed the benchmark value (1 cm 2 V −1 s −1 ) set by hydrogenated amorphous silicon FETs, [5][6][7][8] although the OFET device stability remains a critical obstacle to their commercial use. [ 9,10 ] Bias stress effects, characterized by a drop in the channel current and a detrimental shift in the threshold voltage ( V th ), are commonly observed during the operation of OFETs under a continuously applied bias.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The excellent performance of the diF-TES ADT:PTAA blend is attributed to the vertical phase separation of the two material components that results in a layer of high mobility polycrystalline small-molecule on top of a layer of polymer that acts as a binder. [ 4] [14] [20] This unique microstructure has been shown to reduce the energetic disorder in the transistor channel through the formation of conductive grain boundaries [21] that appear to mediate charge transport between polycrystalline domains. [14] In 2012, the development of the 2 nd generation blend by Smith et al further demonstrated that the choice of polymer binder in the blend is of critical importance, with factors such as electronic energy levels and intrinsic polymer charge carrier mobility values being conducive in attaining organic transistors with very high charge carrier mobilities (>5 cm 2 /Vs).…”
mentioning
confidence: 99%